PEMIKIRAN TAUHID DALAM PEMIKIRAN TASAWUF FALSAFI DAN SUNNI: Tawhid Thought in Falsafi and Sunni Sufism - Dinda Putri Somantri; Achmad Junaedi Sitika (TA'LIMUNA: Jurnal Pendidikan Islam, 2025)
Sufism represents a central dimension of Islam that emphasizes spiritual purification and closeness to Allah SWT through the attainment of pure monotheism (tauhid). Throughout Islamic intellectual history, Sufism has developed into various streams, notably falsafi (philosophical) Sufism and Sunni Sufism, each offering distinct approaches to understanding tauhid. This study aims to describe the characteristics of both streams and to analyze their differences in interpreting tauhid from philosophical and normative perspectives. This research employs a library-based qualitative approach by examining relevant books, journal articles, and contemporary scholarly works. The findings indicate that philosophical Sufism explains tauhid through metaphysical and mystical concepts such as fana’-baqa’, hulul, ittihad, and wahdat al-wujud. In contrast, Sunni Sufism emphasizes the purification of tauhid through adherence to the Qur’an and Hadith, moral cultivation, spiritual discipline, and the balance between shari‘ah and haqiqah. Both streams contribute to enriching the Islamic understanding of tauhid, though each through distinct methods and emphases. Tasawuf merupakan dimensi penting dalam Islam yang menekankan penyucian jiwa serta upaya mendekatkan diri kepada Allah SWT melalui penghayatan tauhid yang murni. Sepanjang sejarah, tasawuf berkembang dalam berbagai corak, di antaranya Tasawuf Falsafi dan Tasawuf Sunni yang memiliki pendekatan berbeda dalam memahami tauhid. Penelitian ini bertujuan mendeskripsikan karakteristik kedua corak tasawuf tersebut dan menjelaskan perbedaannya dalam memaknai tauhid, baik secara filosofis maupun normatif. Metode yang digunakan adalah studi kepustakaan dengan menganalisis buku, artikel jurnal dan penelitian yang relevan. Hasil penelitian menunjukkan bahwa Tasawuf Falsafi memahami tauhid melalui pendekatan filosofis-mistis dengan konsep seperti fana’-baqa’, hulul, ittihad dan wahdat al-wujud. Sementara Tasawuf Sunni menekankan pemurnian tauhid berdasarkan Al-Qur’an dan Hadis melalui praktik akhlak, penyucian jiwa, serta keseimbangan syariat dan hakikat. Kedua corak tasawuf tersebut sama-sama berkontribusi dalam memperkaya pemahaman tauhid, namun melalui jalur dan penekanan yang berbeda.